Pharmacist prescribing in neonatal intensive care units in the UK. Issue 6 (9th May 2013) - Mulholland, P
Abstract : Aims: Primary legislation in the 2001 Health and Social Care Act set the legal basis to allow non-medical prescribing. 1 In March 2003 the Department of Health published a guide for the implementation of supplementary prescribing within the NHS in England. 2 Subsequent legislation changes, culminating with legislation in 2012 allowing non-medical prescribers (NMP) to prescribe Controlled Drugs, 3 means that a NMP now has the same prescribing rights as a medical prescriber. We wanted to determine how far pharmacist prescribing has developed in Neonatal Intensive Care Units (NICU), what benefits are perceived and what barriers have been encountered. Methods: A survey was circulated to NPPG members working in NICU to determine what prescribing was being undertaken, medicines being prescribed, benefits of, and barriers to, pharmacist prescribing Results: 45 responses were received. Just under half (47%) were prescribers, with 40% being independent prescribers. Of those not currently an NMP only 27% had no plans to undertake the course. Most prescribers were prescribing in NICU or Special Care Baby Unit (SCBU) (70%), with some also in out-patients. 19% of those qualified were not prescribing. The main medicines being prescribed were Parenteral Nutrition (PN) (75%), supplements (75%), antibiotics (62%), caffeine (50%) and discharge prescriptions (50%). Two pharmacists had taken advantage of the change in legislation and were prescribing controlled drugs. Only one pharmacist was prescribing clinical trial medicines. Benefits of pharmacist prescribing: Improvement in safety was seen as a benefit of pharmacist prescribing, with potential reduction in communication errors (with the pharmacist making a change in medication or dosage, rather than asking a doctor to do it) and the ability to make timely correction of wrong prescriptions. Pharmacist knowledge of PN and pharmacokinetics were seen to be better utilised with the person advising now also taking the prescribing responsibility. The changes in medical training, with shorter rotas and more emphasis on diagnosis and procedures were seen as an area where NMP was a benefit to the team as a whole. It was also felt that being a prescriber helped the pharmacist to integrate more into the multidisciplinary team. Barriers to implementation: Many areas reported no barriers, with support from consultants and nursing staff. Lack of funding and time to undertake the course were seen as barriers, plus the potential need for a second pharmacist to clinically check what a pharmacist has prescribed. There was a desire for peer support and training to be available to potential prescribers Conclusions: Pharmacist prescribing is not universal in NICUs, but has made significant inroads in this area. The most common areas of prescribing are those that have been identified as most suitable for pharmacist skills at previous NPPG conferences but there is scope to expand practice with experience. Consideration should be given to setting up a peer support network for those contemplating undertaking prescribing in NICU.